LOVE IN ILANA TAN’S NOVEL AUTUMN IN PARIS - Rizki Nurhidayah Sitompul; M. Manugeren; Purwarno Purwarno (Universitas Islam Sumatera Utara, 2019)
The research is concerned with types of love faced by Tara Dupont, the main character of the novel Autumn in Paris, written by Ilana Tan. The types of love: friendship, infatuated love, romantic love and consummate love are the main focus of the study. The objective is to find out how Tara Dupont implements the types of love in relationship with people around her. One of the theories used in the research is Robert Sternberg’s Triangular Theory of Love which states that love has three components: intimacy, passion and commitment and these three components are to be applied to obtain or run real love. Qualitative descriptive method is applied for the whole analysis. The finding shows that types of love are found in the novel Autumn in Paris. Friendship appears in a relationship between Tara, Sebastien and Tatsuya. Romantic love and infatuated love are the dominant types of love and consummate love is the rarest.